Why Indonesia Should Develop Tuna Sea Farming to Overcome Overfishing? A Review of Two Sides Argument - Maharani Yulisti; Rizky Muhartono; Armen Zulham (Balai Besar Riset Sosial Ekonomi Kelautan dan Perikanan, 2014)
Tuna is the mainstay of fisheries export commodities in Indonesia with a total export amounted to 201.159 tons and export value of 750 million dollars in 2012. The high demand tuna improve the practice of tuna captured in the sea, causing a decline in tuna stocks both in the number and size of tuna caught. This condition triggers the experts to culture tuna in laboratory scale to reduce the impact of overexploitation (overfishing). However, the tuna sea farming is under the spotlight because in practice, some countries do tuna farming without hatching of the parent tuna but merely enlarge a baby tuna are caught from the wild to market size. This gives rise to a difference of opinion of many experts on tuna farming practices. Therefore, this article highlights the pros and cons of experts on tuna farming from environmental, economic and technical, to determine whether Indonesia needs to develop tuna farming to cope with overfishing. The method used in this research is the study of literature writings on tuna farming and analyzed descriptively. Results of the analysis showed that despite the many negative opinions about the tuna sea farming, the Indonesian government should support the of tuna sea farming with tuna breeding research, as has been done by the Research Institute for Marine Fisheries Gondol. If the tuna breeding is successful, will have a great impact on the problems of the world tuna demand which increasing every year.